Neurotoxin production and sporulation in Clostridium botulinum Group II type E - Mertaoja, Anna (University of Helsinki, 2024)
The key factors of pathogenesis in clostridial pathogens are toxin production and endospore formation. The toxins cause the clinical symptoms of clostridial diseases by disrupting normal cellular functions and damaging host cells and tissues, while the spores ensure persistence and dispersal in the environment, act as infectious agents, and colonise the host tissues. Understanding how toxin production and sporulation are coordinated in bacterial cells and cultures and uncovering the potential regulatory link between them provides novel intervention points for controlling the risks these pathogens pose to public health and food safety. Clostridium botulinum strains produce the most potent natural toxins, botulinum neurotoxins (BoNTs), that block neurotransmitter release and cause a rare but potentially fatal neuroparalytic disease, botulism. C. botulinum spores are ubiquitous in soil and sediments and may occasionally contaminate food raw materials. In batch cultures, peak BoNT production coincides with the initiation of sporulation, suggesting a regulatory link between the two functions. This study explored the link between BoNT production and sporulation in C. botulinum Group II type E, an aquatic species associated with foodborne botulism in humans and in botulism outbreaks affecting fish and birds. The regulatory link between BoNT production and sporulation was first studied at the population level. The sporulation master switch Spo0A was established as an essential regulator of BoNT production using insertional inactivation of the spo0A gene, and protein-DNA interaction assays showed direct binding of Spo0A to the bontE promoter. Before exploring the coordination of BoNT production and sporulation in Beluga populations on a single-cell level, a sporulation medium enabling high enough sporulation efficiency to simultaneously observe BoNT production and sporulation microscopically was developed, and a novel CRISPR-Cas9 ‘bookmark’ mutagenesis tool was adapted for C. botulinum Beluga to create a markerless spo0A ...